Formulation and Evaluation of Linagliptin Buccal Films: Pharmaceutical sciences- Pharmaceutics - Doijode, Suprith; Mahalingan, K.; Abdul Ahad, Hindustan; Kumar, Pavan; Dhamala, Pawan (International Journal of Life Science and Pharma Research, 2024)
Achieving steady concentration levels of drugs in the plasma for diabetics is important for an extended period. Thestudy focussed on developing mucoadhesive buccal films incorporating linagliptin, aiming to achieve controlled drug delivery foreffective type 2 diabetes management towards steady level plasma concentration. The research utilizes various mucoadhesivepolymers, specifically HPMC K100, HPMC E5LV, and Eudragit RL100, exploring their potential in formulating optimized filmsthrough solvent casting technique. Our primary aim was to identify the most effective formulation, that would ensure controlleddrug release over an extended period. We formulated various formulations and evaluated drug content, swelling index, in-vitrodrug discharge, and ex-vivo mucoadhesive strength. The formulation, incorporated linagliptin, HPMC E5LV, HPMC K100,Eudragit RL100, glycerol, and polyethylene glycol. Results from our comprehensive evaluations showcased favorable dissolutiontime, robust mechanical properties, and impressive mucoadhesive characteristics in the buccal films. The sustained drugdischarge and mucoadhesive strength exhibited by formulation F7 indicate its potential for effective type 2 diabetes managementwith a single film administration lasting up to 8 hours. This research represents a significant step forward in the field ofpharmaceuticals, offering a promising avenue for developing mucoadhesive buccal films to control drug delivery precisely forenhanced therapeutic outcomes in the management of type 2 diabetes.